ANALISIS RANTAI PASOK KOMODITI CABAI RAWIT DI KOTA MANADO - Nathallya Angel Josine; Lyndon R. J. Pangemanan; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the mechanism of supply chain in which there is a flow of products, information flow and financial flows in the city of Manado. Location of the study was determined purposively (purposive sampling), sampling is determined through Accidental Survey. The analytical method used in this research is qualitative descriptive analysis, the procedure in qualitative analysis according to Miles and Huberman (1992), namely Data Reduction, Data Presentation, and Conclusion / Verification. The result of this research is farmer marketing margin value for every kilogram of chili pepper Rp 18.600,00 with farmer profit share equal to 69.5%. The marketing margin value of wholesalers for every one kilogram of cayenne pepper amounted to Rp 4,733.00 with the profit share of wholesalers of 17.7%. The retailer's marketing margin for every one kilogram of cayenne pepper is Rp 3,422.00 with a share of 12.8% profit.